ECONOMIC POTENTIAL AS A KEY ELEMENT OF STRATEGIC MANAGEMENT OF AN AGRICULTURAL ENTERPRISE - KALINICHENKO, Sergiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In modern conditions, the issues of monitoring the current state of the business entity, evaluating and analyzing the use of available resources, and developing and implementing effective management solutions are becoming especially relevant and practical. One of the most acute problems for a modern enterprise is maintaining competitiveness and activity in a constantly changing external environment. The problems of the efficiency of the functioning of agricultural enterprises are related to the use of their potential, which determines the selection and justification based on the conducted economic analysis of procedures for assessing the size and structure of the potential of an agricultural enterprise, which allows it to quickly determine its internal capabilities and shortcomings, to identify hidden reserves. The management of economic potential is aimed at achieving the strategic goals of developing an agricultural enterprise and ensuring its market stability. The rational use of the economic potential of agriculture in the conditions of dynamic growth of the country's economy involves the combination and observance of the optimal proportionality and balance of the development of all components of the potential according to the main parameters of economic growth: high and stable rates, the size of absolute increases, structural shifts in the production volumes of relevant types of products and ensuring its quality The economic potential of an agrarian enterprise is a key element of strategic management, which provides a basis for making informed management decisions. Effective use of economic potential allows enterprises to achieve their strategic goals, adapt to changes in the external environment, and ensure sustainable growth in the long term.
Keywords: potential; management; strategy; development; strategic goals